2016
DOI: 10.18632/oncotarget.12613
|View full text |Cite
|
Sign up to set email alerts
|

S-nitrosation on zinc finger motif of PARP-1 as a mechanism of DNA repair inhibition by arsenite

Abstract: Arsenic, a widely distributed carcinogen, is known to significantly amplify the impact of other carcinogens through inhibition of DNA repair. Our recent work suggests that reactive oxygen/nitrogen species (ROS/RNS) induced by arsenite (AsIII) play an important role in the inhibition of the DNA repair protein Poly(ADP-ribose) polymerase 1 (PARP-1). AsIII-induced ROS lead to oxidation of cysteine residues within the PARP-1 zinc finger DNA binding domain. However, the mechanism underlying RNS-mediated PARP inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Arsenite enhanced UVR- induced oxidative DNA damage by inhibiting the activity and function of PARP-1 (Sun et al, 2014; Zhou et al, 2016). The present study demonstrates that arsenite displaces zinc and inhibits chromatin association of the NER protein XPA in a similar manner to that of PARP-1.…”
Section: Discussionmentioning
confidence: 99%
“…Arsenite enhanced UVR- induced oxidative DNA damage by inhibiting the activity and function of PARP-1 (Sun et al, 2014; Zhou et al, 2016). The present study demonstrates that arsenite displaces zinc and inhibits chromatin association of the NER protein XPA in a similar manner to that of PARP-1.…”
Section: Discussionmentioning
confidence: 99%
“…Both zinc deficiency and arsenic exposure modulate oxidative stress, inflammation, DNA repair and metabolism ( 12 , 21 , 33 , 48 51 ). Correspondingly, our study finds that marginal zinc deficiency and arsenic exposure both independently increased DNA damage and decreased plasma zinc.…”
Section: Discussionmentioning
confidence: 99%
“…Excess NO could cause damage to cells or tissues through targeting DNA, mitochondria, cell membranes and proteins [3,22,23]. Growing body of evidence indicated that NO and NOS-derived NO production are positively correlated with apoptosis [4].…”
Section: Discussionmentioning
confidence: 99%